Novel psychoactive substances as a novel challenge for health professionals: results from an Italian survey. (23rd July 2013) - Simonato, Pierluigi; Corazza, Ornella; Santonastaso, Paolo; Corkery, John; Deluca, Paolo; Davey, Zoe; Blaszko, Ursula; Schifano, Fabrizio
Abstract : Introduction: Novel psychoactive substances (NPS; a.k.a. 'legal highs' or 'smart drugs') are advertised online as 'safe' and 'legal' natural/synthetic analogues of controlled illicit drugs. However, only little research has been carried out in identifying the health professionals' knowledge and expertise relating to the intake of these compounds. Methods: Data presented here refer to the Italian component of the European Union‐wide, European Commission‐funded, ReDNet project survey. An ad‐hoc questionnaire was administered to professionals from the departments of Addiction, Psychiatry, Paediatrics and Emergency Room Services in Italy. Results: The interviewees' sample included 243 professionals, mostly from the departments of Addiction (35%) and Psychiatry (28.4%). Overall, interviewees self‐reported a poor technical knowledge relating to NPS; some 27% of respondents confirmed of not being aware if their patients presented with a previous history of NPS misuse. Discussion: Novel psychoactive substances prevalence of misuse was not considered to be an unusual phenomenon in Italy, and most health professionals appeared to have concerns relating to associated medical and psychopathological risks, especially in terms of aggression/psychomotor agitation. Overall, most respondents reported the need to have better access to NPS‐related reliable sources of information. Copyright © 2013 John Wiley & Sons, Ltd.